2018
DOI: 10.3389/fmars.2018.00251
|View full text |Cite
|
Sign up to set email alerts
|

Cold Water in a Warm World: Investigating the Origin of the Nordic Seas' Unique Surface Properties During MIS 11

Abstract: Surface waters in the Nordic Seas were colder and fresher throughout the marine isotope stage (MIS) 11 interglacial compared to present day. This has been previously attributed to the continuous delivery of freshwater sourced from large ice structures characteristic of the preceding glacial interval, MIS 12. While it is conventionally believed that high-latitude surface freshening can trigger a reduction of the Atlantic Meridional Overturning Circulation (AMOC), multiple lines of evidence suggest a vigorous AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…McManus et al (1999) first showed at ODP Site 980 in the subpolar North Atlantic Ocean that significant suborbital variability over the last 500 ka occurred when ice sheets reached a critical size. This variability was later confirmed by Helmke and Bauch (2003), , and Kandiano et al (2016) for the Nordic seas and in midlatitudes of the northeast North Atlantic by Voelker et al (2010), Rodrigues et al (2011), Doherty and Thibodeau (2018), and Kandiano et al (2017). Figure 4 shows several of these proxy records for the period MIS 12 through MIS 10 (450 to 350 ka) going from north (top, panel 4a) to south (bottom, panel 4j).…”
Section: Paleoceanography and Paleoclimatologymentioning
confidence: 75%
“…McManus et al (1999) first showed at ODP Site 980 in the subpolar North Atlantic Ocean that significant suborbital variability over the last 500 ka occurred when ice sheets reached a critical size. This variability was later confirmed by Helmke and Bauch (2003), , and Kandiano et al (2016) for the Nordic seas and in midlatitudes of the northeast North Atlantic by Voelker et al (2010), Rodrigues et al (2011), Doherty and Thibodeau (2018), and Kandiano et al (2017). Figure 4 shows several of these proxy records for the period MIS 12 through MIS 10 (450 to 350 ka) going from north (top, panel 4a) to south (bottom, panel 4j).…”
Section: Paleoceanography and Paleoclimatologymentioning
confidence: 75%
“…In addition to its user friendliness, the model allows for a mechanistic evaluation of the impact of increased freshwater input on thermohaline circulation through time, which is difficult to achieve analytically. Therefore, SAMDEC provides a robust framework to test the response of thermohaline circulation between the North Atlantic and the Arctic Ocean to changes in freshwater forcing which has possibly played a role in observed temperature and/or salinity gradients in the past (e.g., Bauch et al, 2012;Doherty and Thibodeau, 2018;Kandiano et al, 2016;Thibodeau et al, 2017), as well as in future projections (e.g., IPCC, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The current weak state of the Atlantic meridional overturning circulation (AMOC) is an unprecedented event over the 1,500 years (Caesar et al, 2018;Rahmstorf et al, 2015;Thibodeau et al, 2018;Thornalley et al, 2018). Warming from greenhouse gases and increased high-latitude freshwater fluxes are the main potential culprits for such weakening.…”
Section: Introductionmentioning
confidence: 99%
“…Hearty et al, 2007;Naish et al, 2009;Pollard and DeConto, 2009). However, Pliocene model results were shown to be highly dependent on the choice of climate and ice sheet models (de Boer et al, 2015;Dolan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%